Isolation of Moraxella and Streptococcus from New Packed Orthodontic Materials - Batool Hassan Al-Ghurabi (Journal of Global Pharma Technology, 2016)
This study aimed to test the sterility of new unused orthodontic arch wires received from manufacturers. Forty samples of arch wires with two types of wires (nitinol and stainless steel) from four companies were used directly from the manufactures package in this study. Out of (40) arch wires tested, bacteria was isolated from 3 (7.5%) samples, only two genera of bacteria were isolated, namely Moraxella and Streptococcus. Current results appear that bacterial contamination on arch wires give lights on the need of sterilization before clinical use.Keywords: Orthodontic materials, Arch wires, Microbial contamination.